2005
DOI: 10.1205/fbp.04041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Starch Types on Retardation of Staling of Microwave-baked Cakes

Abstract: D ifferent types of starches (corn, potato, waxy corn, amylomaize and pregelatinized starches) were added to cake formulations to retard staling of microwave-baked cakes. As a control, cake formulated without any starch addition was used. Weight loss, firmness, volume index, specific gravity, soluble starch and amylose content of cakes were used as the indicators of staling and/or quality criteria. Variation of staling parameters during storage of cakes followed zero-order kinetics. Cakes were baked in a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 9 publications
2
28
0
1
Order By: Relevance
“…Increase in water absorption capacity of substituted dough is due to the disrupted granular structure of modified starch as the hydrophobic functional group allow more water to bind (OH) hydroxyl groups via hydrogen bonding (Sweedman et al, 2013). Firmness in bread crumb during storage reflects the process of staling (Seyhun et al, 2005). The present findings are in line with the observations of Hadnadev et al (2013) who found that the hardness value of bread produced from flour containing 10% OSA starch (9879 g) exhibited a declining affect as compared to the control bread (14,910 g).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in water absorption capacity of substituted dough is due to the disrupted granular structure of modified starch as the hydrophobic functional group allow more water to bind (OH) hydroxyl groups via hydrogen bonding (Sweedman et al, 2013). Firmness in bread crumb during storage reflects the process of staling (Seyhun et al, 2005). The present findings are in line with the observations of Hadnadev et al (2013) who found that the hardness value of bread produced from flour containing 10% OSA starch (9879 g) exhibited a declining affect as compared to the control bread (14,910 g).…”
Section: Discussionmentioning
confidence: 99%
“…According to Seyhun, Sumnu and Sahin (2005) change in the hardness of bread crumb is a good indicator of bread aging process because there is a increase of hardness during storage. Increasing in the hardness of bread crumb is due to the reduction of moisture as well as due to the phenomenon of retrogradation (Biliarderis, Izydorczyk and Rattan, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…However, no plateau at low frequency in G 0 was observed for any of the batters, showing that the system was structured but not gelled. G 0 modulus value for batter R at 0.1 rad/s was around 5200 Pa. Due to its capability to absorb water (Seyhun, Sumnu, & Sahin, 2005), partial substitution of the flour by the pregelatinized starches was expected to affect the batter structure and, therefore, its visco-elastic properties. This was reflected by increasing G 0 and G 00 values when PWS or PMS was added (Fig.…”
Section: Batter Formulation Effect On Batter Rheologymentioning
confidence: 99%